Klassizismus in Aktion Goethes Propyläen und das Weimarer Kunstprogramm - Wolf, Norbert Christian (2015)
The collection of essays considers the art journal Propyläen that was edited by Goethe in the years between 1798 and 1800 for the first time as a whole. This enterprise, which was of great significance for the history of aesthetics, will be placed in a new light. The book situates the texts within their historical contexts, and thus provides a key resource for future research, for literary as well as art studies.